VISUAL JOURNALING: A SPRINGBOARD FOR PRIORITISING THE CREATIVE PROCESS? - Maguire, Katie (My University, 2021)
The critical emphasis of the Visual Arts Curriculum for Irish primary schools is on the process of children’s artmaking. Exploration of, and experimentation with materials, is a central objective along with teachers taking a ‘guided discovery’ approach. However, literature and research on the implementation of the Visual Arts Curriculum highlight the need for an innovative approach that prioritises the creative process. In light of this, this study explores the question as to whether the use of visual journaling - “an artistic process for recording personal insights with constructed images and written reflections” (Evans-Palmer, 2018, p.19) - can help to prioritise process in the Visual Arts Curriculum, in the senior end of an Irish primary school. Located within the interpretivist paradigm and employing a mixed-methods design, data was collected from eight primary school teachers in one-case study school through questionnaires, this was followed by an implementation phase where teaches were introduced to visual journaling in their Visual Arts Curriculum, and following this semi-structured focus group interviews were conducted. The first research aim, was to explore the visual art practices of teachers and ascertain factors that may have contributed to the priority of product over process, as identified in School Self-Evaluation prior to this research. The second aim was to introduce teachers, to visual journaling and to investigate and examine its implementation, outcomes and potential to contribute to the prioritisation of process in the Visual Arts Curriculum. Findings from the study confirm that visual journaling served as an effective antidote to the priority on product in the art classroom in the case-study school. Moreover, the research study finds benefits to student learning including enhanced skill, confidence and pride in art-work; improved collaboration and inclusion; creation of a safe space; and increased engagement. The data further evidences benefits to teacher practice including improved implementation of the Visual Arts Curriculum; authentic assessment of student learning; enhanced collaborative practice; and growing confidence in teaching art. A renewed appreciation for a focus on the creative process was also noted. Guided by these findings, it is recommended that visual journaling be highlighted and harnessed as an approach to the prioritisation of the creative process in art education in primary schools.
An Exploration of Teachers’ Perspectives on Visual Journaling in the Primary School Classroom and its Potential to Contribute to the Prioritisation of Process in the Visual Arts Curriculum.
Keywords: Art--Study and teaching (Primary)